2017
DOI: 10.1039/c7ta05030e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a sulfur and nitrogen dual-doped Fe–N–S electrocatalyst for the oxygen reduction reaction

Abstract: A new catalyst with a nitrogen and sulfur dual-doped –Fe–N–S– structure shows excellent ORR activity for AEMFCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Rao and Ishikawa 90 reported 30 hour stability for an MEA using nitrogen-doped carbon nanotube ORR catalysts at a constant current of 20 mA cm À2 . Huang et al reported that the performance of the AEMFC using the transition metal N/S doped carbon ORR catalyst is only 16.5% of the initial value after 1 h. 91 The lowest AEMFC degradation rate using PGM-free ORR catalysts was demonstrated during a 100 h test. Sanetuntikul and Shanmugam reported 8% current density loss of Fe-N-C cathode catalyzed MEA at 60 1C and a constant voltage of 0.4 V in H 2 /O 2 .…”
Section: Current Status Of Aemfc Durabilitymentioning
confidence: 99%
“…Rao and Ishikawa 90 reported 30 hour stability for an MEA using nitrogen-doped carbon nanotube ORR catalysts at a constant current of 20 mA cm À2 . Huang et al reported that the performance of the AEMFC using the transition metal N/S doped carbon ORR catalyst is only 16.5% of the initial value after 1 h. 91 The lowest AEMFC degradation rate using PGM-free ORR catalysts was demonstrated during a 100 h test. Sanetuntikul and Shanmugam reported 8% current density loss of Fe-N-C cathode catalyzed MEA at 60 1C and a constant voltage of 0.4 V in H 2 /O 2 .…”
Section: Current Status Of Aemfc Durabilitymentioning
confidence: 99%
“…The XPS N 1s patterns had four sub-peaks, namely, the pyridinic N group, pyrrolic N group, graphitic N group, and oxidized N group, which corresponded to 398.9, 400.2, 401.7, and 405.3 eV, respectively. ,,, Table lists the corresponding deconvolution results of the two samples. Several studies have reported that, except for oxidized N, the other N-containing groups (i.e., pyridinic N and graphitic N) play crucial roles in the ORR process. ,,, Pyridinic N exerts a conjugation effect on its lone pair of electrons and the π system, facilitating O 2 adsorption and therefore improving ORR activity. , Graphitic N makes neighboring carbons display more positive spin and charge densities, which produce active sites for ORR . The total contents of pyridinic N and graphitic N in Fe–N–Co@C-800-AL are higher than those in Co@C-800-AL, which is consistent with the trends of ORR activity.…”
Section: Resultsmentioning
confidence: 99%
“…Polyelectrolyte fuel cells (PEFCs) have been developed in the past decades. Among them, the anion exchange membrane fuel cell (AEMFC) is a promising candidate because non-precious metal catalysts (NPMCs) are low cost and can be used as electrodes to enhance the activity of oxygen reduction reaction (ORR) as well as improve the stability of NPMCs in an alkaline medium. Recently, transition metal–nitrogen–carbon (M–N–C, MFe, or Co) materials with superior electrocatalytic activity have been regarded as one of the most promising NPMCs in both alkaline and acidic mediums. According to relevant studies, M–N–C materials possess intrinsic ORR active sites (M–N x or N-doped carbon) for improving ORR activity. However, the active sites (M–N x or N-doped carbon) of catalysts remain a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an S and N dual-doped Fe-N-S electrocatalyst (Fe-M-LA/C) was obtained via pyrolysis of the mixture of melamine, lipoic acid, FeCl 3 , and carbon black [24]. FeS and Fe 3 C formed in the Fe-M-LA/C.…”
Section: M-n-s-based Active Sitesmentioning
confidence: 99%